Glass Reflections In Expression Photography - Susanto Umboro (Jurnal Multidisiplin Sahombu, 2025)
An activity that demands creative value in work, the creator tries to process various elements of art to produce interesting and different works from others. Observations of colored glass that is crushed into fragments that are illuminated by natural light (sun) so that it reflects an interesting reflection, then the idea emerged as a basic concept in the process of creating photographic artwork. Glass reflection is a combination of visualization from the seeds of imagination. By exploring the reflection or reflection of colored glass fragments as an object of creating artwork with photography media, the creator believes that the reflection or reflection of glass that is photographed with an extreme macro technique, namely a reversed lens, will present aesthetic images of various patterns, styles, and abstract forms. Photographic works are a visual language practice that contains messages and has a discourse of knowledge and meaning. The photographic work entitled "Glass Reflection in Expression Photography" raises the imaginations that exist within the creator by using reflections or reflections of light from colorful glass shards as a metaphorical expression of what exists and invites art lovers to imagine each by looking at the artwork that the creator produces.